Analisis Kebutuhan Pembelajaran Bahasa Inggris Taruna Program Studi Diploma III Teknologi Pemeliharaan Pesawat Udara Politeknik Penerbangan Makassar - Octavianie, Adhitya; Oktavia, Wahyuni (Politeknik Penerbangan Makassar, 2021)
This research is based on an understanding related to the development of English learning methods that are in line with the demands of the community's needs for English. Apart from the different needs of learners, the needs of the institutions that shelter them are also different. This makes ESP in universities different so that need analysis is very characteristic of the teaching materials used by the ESP program. This study aims to identify the learning needs of students' English related to the four basic English skills, and to know the types of learning methods and teaching materials that students want and need. Respondents in this study were TPPU II Alpha and Bravo cadets at the Makassar Aviation Polytechnic. The method used is descriptive qualitative. The results of this study indicate that the learning needs of students' English related to the four basic skills of English to reach the functional and informational levels are facility (material and practice), and motivation. The types of learning methods and teaching materials that students want and need are CLT Method, and Hybrid Learning.